2021
DOI: 10.1039/d0fo01978j
|View full text |Cite
|
Sign up to set email alerts
|

Deoiled sunflower seeds ameliorate depression by promoting the production of monoamine neurotransmitters and inhibiting oxidative stress

Abstract: SFS may alleviate depression by increasing aromatic neurotransmitters, improving oxidative stress and inflammation and regulating metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…Functional lipids with special fatty acids and/or micronutrients (e.g., phytosterols, tocopherols, polyphenols and other antioxidants) are gaining attention owing to their various health benefits (Guo et al ., 2018; Lu et al ., 2021). They are not only used as cooking oils, shortenings and margarines but also can be used as important constituents in supplements and special medical foods.…”
Section: Introductionmentioning
confidence: 99%
“…Functional lipids with special fatty acids and/or micronutrients (e.g., phytosterols, tocopherols, polyphenols and other antioxidants) are gaining attention owing to their various health benefits (Guo et al ., 2018; Lu et al ., 2021). They are not only used as cooking oils, shortenings and margarines but also can be used as important constituents in supplements and special medical foods.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, CUMS reduced 5-HT levels in the hippocampus, which were restored by chronic administration of DSFS and WPC. In our previous study, WPC and DSFS significantly increased plasma Trp and Trp/LNAAs levels (10). This might be because dietary DSFS and WPC, as direct sources # Represents a significant difference compared with CON group (P < 0.05).…”
Section: Discussionmentioning
confidence: 81%
“…Compared to the S+NE group, aromatic biogenic amine degradation (PWY-7431) in the S+E group showed the most significant upregulation. Studies 44 , 45 have indicated that aromatic biogenic amine acids may have the antidepressant effects. A decrease in the degradation process may cause the accumulation of amines and decrease the levels of amino acids.…”
Section: Discussionmentioning
confidence: 99%